ANALISIS KUALITAS PELAYANAN DAN REPUTASI PERUSAHAAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPERCAYAAN (TRUST) SEBAGAI VARIABEL INTERVENING - giebriel rakha mindie (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2021)
This study uses a sampling technique with purposive sampling method with the criteria of customers who have used tour and travel services 2 times, the sample in this study amounted to 100 respondents. The type of data used in this study is primary data sourced from questionnaires. The instrument test tool uses SPSS for Windows 17.0 while the inferential analysis tool uses Partial Least Square (PLS). The results show that service quality and company reputation have a positive and significant effect on trust and loyalty. Trust mediates the effect of service quality and company reputation on customer loyalty.